The Judges’ Legal Consideration on Divorce of Nushūz Cases at the Kupang High Religious Court: Gender Perspective - Fitriyani, Fitriyani; Saepuddin Jahar, Asep; Subhan, Zaitunah; Rosdiana, Rosdiana (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2023)
The gender sensitivity of judges towards women in court is crucial to ensure that judgments provide a sense of justice and accommodate the rights of wives after divorce. This article aims to analyze judges' considerations from philosophical, juridical, and sociological aspects in divorce judgments due to nushūz (disobedience) from a gender perspective, addressing two main questions: 1) how judges use a gender perspective in deciding divorce cases due to nushūz, and 2) what factors influence judges' decisions in divorce cases due to nushūz from a gender perspective. This research employs qualitative research methods, which is a case study design, with juridical and gender approaches. The primary data source is derived from the rulings of the Religious High Court of Kupang No. 009/Pdt.G/2015/PTA.Kp obtained from the Supreme Court of the Republic of Indonesia's website, and judge interviews as supporting data, which were analyzed using content analysis. The research findings indicate that from a gender perspective, judges exhibit gender bias in categorizing nushūz as if nushūz can only be committed by wives, whereas nushūz can be committed by both husbands and wives. Judges' interpretations of nushūz are still influenced by the content of the law, the culture of the law, and its structure of the law. This study implies that judges should undergo gender-based training or workshops organized by judicial institutions or universities to enhance their gender sensitivity in deciding legal cases, especially nushūz cases.